Visualizando Comunalidades e Variabilidades em uma Família de Produtos de Software - da Costa, Denise Alves; dos Santos Neto, Pedro de Alcântara (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2019: Anais do XV Simpósio Brasileiro de Sistemas de Informação, 2019)
Usually, the software development companies have a lot of variants of the same product to different clients.The engineering of Software Product Line (SPL) decrease development process effort compared to traditional methodology. However, the migration from existing variant systems to one SPL can be a costly task. Various approaches have been proposed to perform this process. This work, in turn, proposes support companies by a semi-automatic method to commonalities and variabilities identification and visualization for a set of products variants. We evaluate our proposed method on variant information systems of a software development company. The proposed method helped the volunteers identify the commonalities and variabilities among the variant information systems, thus representing a fundamental support to SPL adoption in a software development company.